Prevalence and predictors of poor sleep quality among secondary school students in Gombak, Selangor, Malaysia - Appanna, Kesintha Devi (2017)
Poor sleep quality among adolescents is becoming a major worldwide concern and widely recognized as a significant public health issue. Increasing school, family, social pressure and environmental issues among adolescents indirectly lead to a delay of sleep timing together with the change in the intrinsic regulation of both circadian and homeostatic processes. In Malaysia, the prevalence of poor sleep quality is high, 30-67% reported among university students and working adults. However, there has been no study on poor sleep quality among secondary school students in Malaysia found to date. Thus, this study was conducted to determine the prevalence and predictors of poor sleep quality among secondary school students in Gombak , Selangor. A cross-sectional study was conducted among 1016 secondary school students of form 1, 2, and 4 in two government secondary schools in Gombak District using sampling with probability to proportionate to size from July 2015 to September 2015. Self-administered pretested questionnaires were used to capture socio-demographic characteristic, academic performance and psychological factor (depression, anxiety, and stress). Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) and further distinguished from “poor” to “good” sleep quality. The response rate was 93.0%. The prevalence of poor sleep quality was 24.0% (95% CI = 21.5, 26.6). Highest prevalence (34.1%) of poor sleep quality was among 16 to <17 year old students. Females (28.1%) had significantly higher prevalence of poor sleep quality compared to males (21.3%). Students with divorced or widow parents (60.9 %) had significantly higher proportion of poor sleep quality than those with married parents (17.6%)(χ2= 132.42, df =1, p<0.001). Students reporting depression (42.1%) had significantly higher proportion of poor sleep quality compared to those with no depression (8.1%) (χ2=159.96, df =1, p<0.001). Students reporting anxiety (41.4%) had significantly higher proportion of poor sleep quality than those with no anxiety (4.8%) (χ2= 186.11, df =1, p<0.001). Prevalence of poor sleep quality was also significantly higher among those reporting stress (39.9%) than those not reporting stress (8.2%) (χ2= 139.74, df =1, p<0.001) and among those who scored poorly in their examination (45.6 %) compared to those scoring well (6.9%) (χ2= 172.19, df =1, p<0.001). Multiple logistic regression was used to determine the predictors of poor sleep quality and the significant and independent predictors of poor sleep quality as follows: aged 16 to <17 years (adjusted OR=3.10, 95% CI= 1.19, 8.05, p=0.02), divorced or widow parents (adjusted OR=6.21, 95% CI=3.63, 10.29, p<0.001), depression (adjusted OR=5.42, 95% CI= 3.45, 8.54, p<0.001), anxiety (adjusted OR=8.68, 95% CI= 5.13, 14.71, p=0.001), stress (adjusted OR=4.27, 95% CI =2.70, 6.77, p<0.001) and poor and average academic performance (adjusted OR=5.83, 95% CI= 3.43, 10.02, p<0.001) and (adjusted OR=3.67, 95% CI= 2.14, 6.39, p<0.001) respectively. In conclusion, the prevalence of poor sleep quality was 24%, considerably high among secondary school students. Older age group, divorced or widow parents, depression, anxiety, stress and poor-average academic performance were the independent predictors of poor sleep quality among secondary school students. A cohort study is needed to confirm the factors associated with poor sleep quality among secondary school students.